THE ROLE OF LOCUS OF CONTROL AS A MEDIATION VARIABLE ON THE INFLUENCE OF FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, FINANCIAL EXPERIENCE ON FINANCIAL MANAGEMENT BEHAVIOR - Noviyanti, Lili; Setiawati, Ira; Darmaputra, Fadjar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to test and analyze the influence of Financial Attitude, Financial Knowledge, Financial Experience on Financial Management Behavior with Locus of Control as a mediating variable. The method determined in this research is a quantitative method by distributing questionnaires. The sample selection technique uses purposive sampling with the criteria of students making investments. The population used in this research were the 7 largest PTNs and PTSs in Semarang City, with a total sample of 385 PTN and PTS Student Investor respondents in Semarang City. This research uses the Partial Least Structural Equation model (SEM-PLS) with SmartPLS 4 software to test and analyze the data. Based on the research that has been carried out, the research results found that Financial Attitude has a positive and significant influence on Financial Management Behavior, Financial Knowledge has no significant influence on Financial Management Behavior, Financial Experience has a positive and significant influence on Financial Management Behavior, Locus of Control has a positive and significant influence on Financial Management Behavior, Financial Attitude has a positive and significant effect on Financial Management Behavior through Locus of Control as a mediating variable, Financial Knowledge has a positive and significant effect on Financial Management Behavior through Locus of Control as a mediating variable, Financial Experience has a positive and significant effect on Financial Management Behavior through Locus of Control as a mediating variable.